Polypropylene imitation steel fiber permeable concrete and preparation method thereof
By optimizing the doping and length of polypropylene imitation steel fibers and introducing reinforced components, the fiber clumping problem is solved, significantly improving the mechanical properties and water permeability of permeable concrete, ensuring its application in urban road construction.
Patent Information
- Application Number
- CN202410672502.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-05-28
AI Technical Summary
Polypropylene imitation steel fibers are prone to fiber clumping during mixing, resulting in poor dispersion of concrete and affecting its mechanical properties and water permeability.
By optimizing the aggregate particle size, fiber dosage and fiber length, and introducing reinforcement components such as ethyl orthosilicate, acrylic and silane coupling agents, the interface bonding performance between fiber and cement matrix is improved and the mechanics of the material is improved. Performance and durability.
It effectively avoids fiber clumping, improves the compressive, flexural strength and water permeability of concrete, and enhances its durability under different environmental conditions.
Smart Images

Figure CN118479809B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a polypropylene imitation steel fiber permeable concrete and a preparation method thereof. Background Art
[0002] With the continuous progress of urban construction, road infrastructure construction faces new challenges and opportunities. The emergence of new concepts such as sponge cities and resilient cities not only puts forward higher requirements for urban construction, but also brings new development directions. Against this background, building a three-dimensional ecological integrated transportation system and promoting the green development of transportation infrastructure have become the inevitable choice of the times. In particular, the proposal and practice of the "sponge city" concept emphasizes urban flood control and drainage, the rational use of water resources and the restoration of the ecological environment, which has a profound impact on urban infrastructure construction.
[0003] As a new type of environmentally friendly material, permeable concrete has become an indispensable material in urban road construction with its good permeability and high strength. Its main advantage is that it can effectively solve the problem of urban road surface waterlogging, while raising the groundwater level and promoting the improvement of the urban water circulation system. However, permeable concrete still has certain shortcomings during use - that is, how to further improve its mechanical properties while maintaining high permeability has become the focus of research.
[0004] In recent years, in order to solve this problem, many scholars at home and abroad have begun to explore the improvement of the mechanical properties of permeable concrete by adding various inorganic fibers. Among them, polypropylene imitation steel fiber is considered to be an ideal reinforcement material because of its low carbon, environmental protection, high strength and corrosion resistance. By adding polypropylene imitation steel fiber to permeable concrete, the tensile and compressive strength of concrete can be effectively improved, thereby extending its service life and reducing the frequency of maintenance and replacement.
[0005] However, there are still few studies on polypropylene imitation steel fiber reinforced permeable concrete, which limits its application and promotion in urban road construction. Comprehensive research from the microstructure to the macroscopic mechanical properties of the material, from theoretical analysis to the exploration of practical applications, are the key directions of current and future research. In addition, exploring the interfacial bonding performance between polypropylene imitation steel fibers and the concrete matrix, as well as the durability under different environmental conditions, is also the key to ensuring the long-term serviceability of permeable concrete. For example, the Chinese invention patent, public announcement number: CN113880527A, its technical solution is as follows: "Using concrete as the matrix, organic imitation steel fibers and water-based epoxy resin emulsions of different lengths and dosages are evenly added to the concrete matrix to obtain organic imitation steel fiber polymer concrete. The proportions of each component are: concrete matrix 2020-3230kg / m 3 ; Water-based epoxy resin emulsion 41-45kg / m 3; Water-based epoxy curing agent 10.25-11.25kg / m 3 ; Defoamer 4.1-4.5kg / m 3 ; Organic imitation steel fiber 2.76-5.52kg / m 3 ; Water margin "; The solution has the following problems: after the fiber content or length increases to a certain value, the mutual entanglement and aggregation of different fibers become more and more obvious, resulting in poor fiber dispersion. This fiber agglomeration not only affects the uniformity of concrete and reduces its workability, but also affects the mechanical properties of concrete such as compressive strength and tensile strength, and also affects its water permeability. When the fibers agglomerate, a large unreinforced area will be formed in the concrete, which can neither play the reinforcing effect of the fibers nor become the source of later cracks. In addition, agglomeration will reduce the fluidity of the mixture, increase the difficulty of construction, and affect the quality and efficiency of the project.
[0006] In summary, the promotion and application of permeable concrete reinforced with polypropylene imitation steel fiber in road infrastructure construction can not only meet the high standards of modern cities for ecology and environmental protection, but also effectively improve the durability and service performance of roads, which has extremely important practical significance and broad development prospects. Therefore, increasing the research on permeable concrete reinforced with polypropylene imitation steel fiber and promoting its application in urban road construction will play an important role in achieving sustainable urban development. Summary of the invention
[0007] 1. Problems to be solved
[0008] There is a complete process for the preparation of polypropylene imitation steel fiber permeable concrete, but when the fiber content or length increases to a certain value, the fiber "clumping" phenomenon cannot be avoided, that is, the complete dispersion of polypropylene imitation steel fiber during the mixing process is a problem that relevant personnel in this field urgently need to solve. The present invention provides a polypropylene imitation steel fiber permeable concrete with excellent performance and multiple functions and a preparation method thereof. As a pavement material for urban road paving, it has the characteristics of high strength and good permeability. At the same time, the materials selected for preparation have the characteristics of low carbon and environmental protection.
[0009] 2. Technical solution
[0010] To solve the above problems, the technical solution provided by the present invention is:
[0011] A polypropylene imitation steel fiber permeable concrete, comprising the following raw materials in parts by weight:
[0012]
[0013]
[0014] The reinforcing components include the following components in parts by weight:
[0015] 30-60 parts of ethyl orthosilicate,
[0016] Acrylic acid 40-60 parts,
[0017] Silane coupling agent 2-10 parts.
[0018] The polypropylene imitation steel fiber permeable concrete described above,
[0019] The polypropylene imitation steel fiber permeable concrete includes the following raw materials in parts by weight:
[0020] The reinforcing components include the following components in parts by weight:
[0021] 40-50 parts of ethyl orthosilicate,
[0022] Acrylic acid 45-55 parts,
[0023] Silane coupling agent 4-8 parts.
[0024] The polypropylene imitation steel fiber permeable concrete described above,
[0025] The polypropylene imitation steel fiber permeable concrete includes the following raw materials in parts by weight:
[0026] The reinforcing components include the following components in parts by weight:
[0027] 45 parts of ethyl orthosilicate,
[0028] Acrylic acid 50 parts,
[0029] Silane coupling agent 6 parts.
[0030] The polypropylene imitation steel fiber permeable concrete described above,
[0031] The aggregate gradation of the melon seed stone is 5mm-10mm;
[0032] The cement is silicate cement with a strength grade of PO 42.5;
[0033] The content of the silica fume is as follows: by weight percentage, 1.2%-1.5% iron oxide, 2%-4% aluminum oxide, 1.6%-2.4% calcium oxide, 0.3%-0.8% magnesium oxide, and the balance is silicon dioxide.
[0034] The polypropylene imitation steel fiber permeable concrete described above,
[0035] The water reducing agent is produced by BASF AG of Germany. FS20 type water reducing agent;
[0036] The smooth polypropylene imitation steel fiber has a length of 15 mm to 45 mm, a diameter of 0.8 mm, a tensile strength of 540 MPa, and an elastic modulus of 6000 MPa.
[0037] The polypropylene imitation steel fiber permeable concrete described above,
[0038] The silane coupling agent is 3-methacryloxypropyltrimethoxysilane or vinyltrimethoxysilane.
[0039] A method for preparing the polypropylene imitation steel fiber permeable concrete as described above,
[0040] The following steps are involved:
[0041] (1) All the melon seeds used in the test were cleaned to remove surface sand and impurities, dried in a drying oven and sieved to obtain a single size;
[0042] (2) pouring the melon seed stone, cement, silica fume, reinforcing component, and water reducing agent obtained in step (1) into a single-horizontal shaft mixer and stirring and mixing them thoroughly to obtain a premix; adding water to the premix and continuing to stir until the slurry has good fluidity and no dry material is visually observed to obtain a mixture;
[0043] (3) dispersing the smooth polypropylene imitation steel fiber into multiple uniform portions, and gradually adding the portions into the mixture obtained in step (2) to obtain a fiber mixed slurry;
[0044] (4) placing the mold coated with a release agent in advance on a vibration table, placing a pre-assembled baffle around the outer edge of the mold, injecting the fiber mixed slurry mixed in step (3) into the mold, turning on the vibration table, and after the vibration is completed, gently scraping off the excess slurry with a scraper and leveling the top surface;
[0045] (5) After pouring, cover with plastic film, cure at room temperature for 72 hours and then demould. Place the demoulded specimen in a standard curing box and cure in water at a constant temperature of 20±2℃ until the specified age.
[0046] The preparation method of the polypropylene imitation steel fiber permeable concrete described above,
[0047] The drying temperature in the drying oven in step (1) is 85°C;
[0048] The stirring speed of the premix in step (2) is 20 rpm;
[0049] The stirring time of the premix in step (2) is 60s;
[0050] The stirring speed of the mixture in step (2) is 20 rpm;
[0051] The stirring time of the mixture in step (2) is 120s.
[0052] The preparation method of the polypropylene imitation steel fiber permeable concrete described above,
[0053] In step (3), the stirring time of the fiber mixed slurry when adding each portion of smooth polypropylene imitation steel fiber is 15 seconds;
[0054] The vibration time in step (4) is 3s.
[0055] The preparation method of the polypropylene imitation steel fiber permeable concrete described above,
[0056] The age period specified in step (5) is 28 days.
[0057] 3. Beneficial effects
[0058] There are many limitations in existing permeable concrete materials. For example, although ordinary permeable concrete has the function of water permeability, it has insufficient compressive strength, is easy to break, and has poor durability. Although asphalt permeable concrete can adapt to changing climatic conditions, it is easy to soften and age at high temperatures, which limits its application range. Although epoxy resin permeable concrete has good mechanical properties, its high preparation cost and poor weather resistance limit its practical application.
[0059] The polypropylene imitation steel fiber permeable concrete introduced in the present invention uses polypropylene imitation steel fiber as a reinforcement material, which not only has excellent mechanical properties and can effectively improve the compression, flexural and durability of concrete, but also has significant advantages in terms of economy because its raw materials are easily available and inexpensive. In addition, the material has good environmental adaptability and exhibits stable performance regardless of extremely cold or extremely hot climate conditions, greatly expanding its application field.
[0060] Through a series of studies and experiments, the present invention optimizes the aggregate (melon seed stone) particle size, fiber content and fiber length. These optimization strategies further enhance the mechanical properties and durability of the material. The application of polypropylene imitation steel fiber not only achieves a leapfrog development in material performance in technology, but also makes an important supplement to the existing permeable concrete materials from the perspective of environmental protection. Its low-carbon and environmentally friendly characteristics are in line with the current pursuit of sustainable development, especially in the construction of ecological projects such as "sponge cities", showing important application value.
[0061] At the same time, the present invention also innovatively introduces reinforcing components, specifically, to achieve the following functions: (1) Improve the interfacial bonding performance: Silane coupling agent forms an intermediate layer on the surface of polypropylene imitation steel fiber, which greatly enhances the bonding between fiber and cement matrix, avoiding interfacial slip and fiber pull-out, which is crucial to the performance of fiber-reinforced composite materials. (2) Improve microstructure: Ethyl orthosilicate forms a silicate network structure inside the concrete through hydrolysis and condensation reaction, which can fill the area with higher porosity and improve the density and uniformity of the material. (3) Increase durability: Acrylic acid can not only enhance adhesion, but also form a protective film on the surface of concrete, increasing the waterproof performance and chemical corrosion resistance of the concrete after mixing. (4) Control the water reduction effect: The addition of acrylic acid helps to optimize the rheological properties of concrete slurry, which means that the amount of water used can be reduced without reducing fluidity, thereby improving the strength and durability of the hardened concrete. (5) Enhance mechanical properties: In concrete, the reinforcing components are combined with traditional cement-based materials to improve crack resistance and bearing capacity, reduce the speed of crack development, and help protect the structure from damage caused by excessive stress.
[0062] Furthermore, the polypropylene imitation steel fiber permeable concrete provided by the present invention, while enhancing the comprehensive performance of the material, also focuses on sustainable development and ecological environmental protection. It not only improves the quality and life of urban infrastructure by improving the many shortcomings of traditional permeable concrete, but also contributes to the research and development and application of green building materials. The widespread application of this innovative material will effectively promote the improvement of urban drainage systems, increase the infiltration and recovery of surface water, and contribute to the maintenance of urban water circulation and ecological balance. Therefore, the polypropylene imitation steel fiber permeable concrete of the present invention can not only improve the performance of public facilities such as roads and squares, but also play an important role in environmental protection and energy saving, making a significant contribution to the sustainable development of cities. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 It is the apparent image of polypropylene imitation steel fiber;
[0064] Figure 2 This is a flow chart for preparing polypropylene imitation steel fiber permeable concrete in an embodiment of the present invention;
[0065] Figure 3 It is the 28d compressive strength of polypropylene imitation steel fiber permeable concrete;
[0066] Figure 4 It is the 28d flexural strength of polypropylene imitation steel fiber permeable concrete;
[0067] Figure 5 It is the stress-strain diagram of polypropylene imitation steel fiber permeable concrete;
[0068] Figure 6 It is the permeability coefficient diagram of polypropylene imitation steel fiber permeable concrete;
[0069] Figure 7 It is the porosity diagram of polypropylene imitation steel fiber permeable concrete;
[0070] Figure 8 This is a scanning electron microscope photo of polypropylene imitation steel fiber permeable concrete after destruction. DETAILED DESCRIPTION
[0071] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0072] It should be noted that the weight parts involved in the present invention are only relative units, and kg (kilogram) can be selected for practical application.
[0073] The raw materials used in the examples are:
[0074] The cement used in this test is ordinary Portland cement with a strength grade of PO 42.5. The physical properties are shown in Table 1. Silica fume is selected as the auxiliary cementitious material, and the properties are shown in Table 2. Melon seeds produced in Guangdong are selected, and the aggregate grading is 5mm-10mm. Polycarboxylic acid high-efficiency water reducing agent is selected. The reinforcement material used in the test is polypropylene imitation steel fiber, with a dosage of 6kg / m 3 ; Lengths are 15, 30, and 45 mm; Shapes are smooth, embossed, and wavy; Diameter is 0.8 mm, tensile strength is 540 MPa, and elastic modulus is 6000 MPa.
[0075] Table 1 Physical properties of ordinary Portland cement
[0076]
[0077] Table 2 Physical properties of silica fume
[0078] <![CDATA[Specific surface area (m 2 / g)]]> Loss on ignition Water demand ratio Activity Index Alkali content 21 1.48% 112% 105% 0.18%
[0079] Example 1
[0080] The present embodiment provides a polypropylene imitation steel fiber permeable concrete, which is composed of the following components by mass: 1531 parts of melon seed stone (particle grading 5mm-10mm), 341.19 parts of cement, 113.7 parts of water, 37.91 parts of silica fume, 2 parts of water reducer, and 6 parts of smooth polypropylene imitation steel fiber; the length of the polypropylene imitation steel is 30mm; the water-binder ratio is 0.3; the porosity of the polypropylene imitation steel fiber permeable concrete is 20%;
[0081] The amount of the reinforcing component is 10 parts; wherein the reinforcing component, by weight, includes the following components:
[0082] 30 parts of ethyl orthosilicate,
[0083] Acrylic acid 60 parts,
[0084] Silane coupling agent 2 parts.
[0085] The preparation method of the polypropylene imitation steel fiber permeable concrete is composed of the following steps:
[0086] (1) All the melon seeds used in the test were cleaned to remove surface sand and impurities, dried in a drying oven and sieved to obtain a single size (drying oven temperature 85°C).
[0087] (2) Pour solid powder (cement, silica fume, reinforcing component, water reducing agent) and aggregate into a single-shaft mixer and stir and mix thoroughly to obtain a premix (the stirring time of the premix is 60 seconds); add water to the premix and continue stirring until the slurry has good fluidity and no dry material is visually observed to obtain a mixture (the stirring time of the mixture is 120 seconds);
[0088] (3) Divide the polypropylene imitation steel fiber into 5 equal parts, and try to disperse the polypropylene imitation steel fiber as much as possible. After completing step 2, continue to run the mixer, and sprinkle each portion of the polypropylene imitation steel fiber into the mixture, sprinkle the fiber into the mixture while stirring, and repeat this step several times until all the polypropylene imitation steel fiber is added to obtain a fiber mixed slurry (the stirring time of the fiber mixed slurry when adding each portion of fiber is 15s);
[0089] (4) Place the mold (mold size 100mm×100mm×100mm) coated with release agent in advance on the vibration table, place a pre-assembled 50mm high baffle around the outer edge of the mold, inject the mixed fiber mixture slurry into the mold and reach 2 / 3 of the outer edge baffle, turn on the vibration table switch and vibrate for 3s. After the vibration is completed, use a scraper to gently scrape off the excess slurry and level the top surface to avoid applying external force loads.
[0090] (5) After pouring, cover with plastic film to prevent moisture loss. Curing the specimen under film at room temperature for 72 h, demoulding, and placing the demoulding specimen in a standard curing box at a constant temperature of 20±2℃ to the specified age.
[0091] Example 2
[0092] The present embodiment provides a polypropylene imitation steel fiber permeable concrete, which is composed of the following components by mass: 1531 parts of melon seed stone (particle grading 5mm-10mm), 341.19 parts of cement, 113.7 parts of water, 37.91 parts of silica fume, 2 parts of water reducer, and 6 parts of embossed polypropylene imitation steel fiber; the length of the polypropylene imitation steel fiber is 30mm; the water-binder ratio is 0.3; the porosity of the polypropylene imitation steel fiber permeable concrete is 25%;
[0093] The amount of the reinforcing component is 10 parts; wherein the reinforcing component, by weight, includes the following components:
[0094] 60 parts of ethyl orthosilicate,
[0095] 40 parts of acrylic acid,
[0096] 10 parts of silane coupling agent.
[0097] The preparation method of the polypropylene imitation steel fiber permeable concrete is composed of the following steps:
[0098] (1) All the melon seeds used in the test were cleaned to remove surface sand and impurities, dried in a drying oven and sieved to obtain a single size (drying oven temperature 85°C).
[0099] (2) Pour solid powder (cement, silica fume, reinforcing component, water reducing agent) and aggregate into a single-shaft mixer and stir and mix thoroughly to obtain a premix (the stirring time of the premix is 60 seconds); add water to the premix and continue stirring until the slurry has good fluidity and no dry material is visually observed to obtain a mixture (the stirring time of the mixture is 120 seconds);
[0100] (3) Divide the polypropylene imitation steel fiber into 5 equal parts, and try to disperse the polypropylene imitation steel fiber as much as possible. After completing step 2, continue to run the mixer, and sprinkle each portion of the polypropylene imitation steel fiber into the mixture, sprinkle the fiber into the mixture while stirring, and repeat this step several times until all the polypropylene imitation steel fibers are added to obtain a fiber mixed slurry (the stirring time of the fiber mixed slurry when adding each portion of fiber is 15s);
[0101] (4) Place the mold (mold size 100mm×100mm×100mm) coated with release agent in advance on the vibration table, place a pre-assembled 50mm high baffle around the outer edge of the mold, inject the mixed fiber mixture slurry into the mold and reach 2 / 3 of the outer edge baffle, turn on the vibration table switch and vibrate for 3s. After the vibration is completed, use a scraper to gently scrape off the excess slurry and level the top surface to avoid applying external force loads.
[0102] (5) After pouring, cover with plastic film to prevent moisture loss. Curing the specimen under film at room temperature for 72 h, demoulding, and placing the demoulding specimen in a standard curing box at a constant temperature of 20±2℃ to the specified age.
[0103] Example 3
[0104] The present embodiment provides a polypropylene imitation steel fiber permeable concrete, which is composed of the following components by mass: 1531 parts of melon seed stone (particle grading 5mm-10mm), 341.19 parts of cement, 113.7 parts of water, 37.91 parts of silica fume, 2 parts of water reducer, and 6 parts of corrugated polypropylene imitation steel fiber; the length of the polypropylene imitation steel fiber is 15mm; the water-binder ratio is 0.3; the porosity of the polypropylene imitation steel fiber permeable concrete is 23%;
[0105] The amount of the reinforcing component is 10 parts; wherein the reinforcing component, by weight, includes the following components:
[0106] 40 parts of ethyl orthosilicate,
[0107] Acrylic acid 50 parts,
[0108] Silane coupling agent 5 parts.
[0109] The preparation method of the polypropylene imitation steel fiber permeable concrete is composed of the following steps:
[0110] (1) All the melon seeds used in the test were cleaned to remove surface sand and impurities, dried in a drying oven and sieved to obtain a single size (drying oven temperature 85°C).
[0111] (2) Pour solid powder (cement, silica fume, reinforcing component, water reducing agent) and aggregate into a single-shaft mixer and stir and mix thoroughly to obtain a premix (the stirring time of the premix is 60 seconds); add water to the premix and continue stirring until the slurry has good fluidity and no dry material is visually observed to obtain a mixture (the stirring time of the mixture is 120 seconds);
[0112] (3) Divide the chopped fibers into 5 equal parts, and try to disperse the polypropylene imitation steel fibers as much as possible. After completing step 2, continue to run the mixer, and sprinkle each portion of the polypropylene imitation steel fibers into the mixture, sprinkle the fibers into the mixture while stirring, and repeat this step several times until all the polypropylene imitation steel fibers are incorporated to obtain a fiber mixed slurry (the stirring time of the fiber mixed slurry when adding each portion of fiber is 15 seconds);
[0113] (4) Place the mold (mold size 100mm×100mm×100mm) coated with release agent in advance on the vibration table, place a pre-assembled 50mm high baffle around the outer edge of the mold, inject the mixed fiber mixture slurry into the mold and reach 2 / 3 of the outer edge baffle, turn on the vibration table switch and vibrate for 3s. After the vibration is completed, use a scraper to gently scrape off the excess slurry and level the top surface to avoid applying external force loads.
[0114] (5) After pouring, cover with plastic film to prevent moisture loss. Curing the specimen under film at room temperature for 72 h, demoulding, and placing the demoulding specimen in a standard curing box at a constant temperature of 20±2℃ to the specified age.
[0115] Example 4
[0116] The present embodiment provides a polypropylene imitation steel fiber permeable concrete, which is composed of the following components by mass: 1531 parts of melon seed stone (particle grading 5mm-10mm), 341.19 parts of cement, 113.7 parts of water, 37.91 parts of silica fume, 2 parts of water reducer, and 6 parts of corrugated polypropylene imitation steel fiber; the length of the polypropylene imitation steel fiber is 30mm; the water-binder ratio is 0.3; the porosity of the polypropylene imitation steel fiber permeable concrete is 22%;
[0117] The amount of the reinforcing component is 10 parts; wherein the reinforcing component, by weight, includes the following components:
[0118] 35 parts of ethyl orthosilicate,
[0119] Acrylic acid 55 parts,
[0120] Silane coupling agent 3 parts.
[0121] The preparation method of the polypropylene imitation steel fiber permeable concrete is composed of the following steps:
[0122] (1) All the melon seeds used in the test were cleaned to remove surface sand and impurities, dried in a drying oven and sieved to obtain a single size (drying oven temperature 85°C).
[0123] (2) Pour solid powder (cement, silica fume, reinforcing component, water reducing agent) and aggregate into a single-shaft mixer and stir and mix thoroughly to obtain a premix (the stirring time of the premix is 60 seconds); add water to the premix and continue stirring until the slurry has good fluidity and no dry material is visually observed to obtain a mixture (the stirring time of the mixture is 120 seconds);
[0124] (3) Divide the polypropylene imitation steel fiber into 5 equal parts, and try to disperse the polypropylene imitation steel fiber as much as possible. After completing step 2, continue to run the mixer, and sprinkle each portion of the polypropylene imitation steel fiber into the mixture, sprinkle the fiber into the mixture while stirring, and repeat this step several times until all the polypropylene imitation steel fiber is added to obtain a fiber mixed slurry (the stirring time of the fiber mixed slurry when adding each portion of fiber is 15s);
[0125] (4) Place the mold (mold size 100mm×100mm×100mm) coated with release agent in advance on the vibration table, place a pre-assembled 50mm high baffle around the outer edge of the mold, inject the mixed fiber mixture slurry into the mold and reach 2 / 3 of the outer edge baffle, turn on the vibration table switch and vibrate for 3s. After the vibration is completed, use a scraper to gently scrape off the excess slurry and level the top surface to avoid applying external force loads.
[0126] (5) After pouring, cover with plastic film to prevent moisture loss. Curing the specimen under film at room temperature for 72 h, demoulding, and placing the demoulding specimen in a standard curing box at a constant temperature of 20±2℃ to the specified age.
[0127] Comparative Example 1
[0128] This embodiment provides an ordinary permeable concrete, which is composed of the following components in parts by mass: 1531 parts of melon seed stone (particle grading 5mm-10mm), 341.19 parts of cement, 113.7 parts of water, 37.91 parts of silica fume, and 2 parts of water reducing agent; the porosity of the permeable concrete is 20-25%.
[0129] The preparation method of the above-mentioned ordinary permeable concrete consists of the following steps:
[0130] (1) All the melon seeds used in the test were cleaned to remove surface sand and impurities, dried in a drying oven and sieved to obtain a single size (drying oven temperature 85°C).
[0131] (2) Pour solid powder (cement, silica fume, reinforcing component, water reducing agent) and aggregate into a single-shaft mixer and stir and mix thoroughly to obtain a premix (the stirring time of the premix is 60 seconds); add water to the premix and continue stirring until the slurry has good fluidity and no dry material is visually observed to obtain a mixture (the stirring time of the mixture is 120 seconds);
[0132] (3) Place the mold (mold size 100mm×100mm×100mm) coated with release agent in advance on the vibration table, place a pre-assembled 50mm high baffle around the outer edge of the mold, inject the mixed fiber mixture slurry into the mold and reach 2 / 3 of the outer edge baffle, turn on the vibration table switch and vibrate for 3s. After the vibration is completed, use a scraper to gently scrape off the excess slurry and level the top surface to avoid applying external force loads.
[0133] (4) After pouring, cover with plastic film to prevent moisture loss. Curing the specimen under film at room temperature for 72 h, demoulding, and placing the demoulding specimen in a standard curing box at a constant temperature of 20±2℃ to the specified age.
[0134] Test method:
[0135] Mechanical properties test of polypropylene imitation steel fiber permeable concrete:
[0136] Compressive strength: The permeable concrete compressive test specimens are 100mm*100mm*100mm cubes, with 3 specimens in each group. The test is carried out in accordance with the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T50081-2019); the test is completed on a microcomputer-controlled electro-hydraulic servo pressure testing machine.
[0137] 28d compressive strength of polypropylene imitation steel fiber permeable concrete: Figure 3 It can be seen that the best mechanical property is the corrugated polypropylene imitation steel fiber, and as the length of the polypropylene imitation steel increases, the compressive strength first increases and then decreases. The optimal fiber length is 30mm, and its compressive strength is 22.78MPa, which is 16.17% higher than the compressive strength of comparative example 1 (without adding fiber).
[0138] Flexural strength: The flexural strength test specimens are 100mm*100mm*400mm prisms, with 3 specimens in a group. The test is carried out in accordance with the "Standard for Test Methods for Mechanical Properties of Ordinary Concrete" (GB / T50081-2019); the test is completed on a microcomputer-controlled electro-hydraulic servo pressure testing machine.
[0139] 28d flexural strength of polypropylene imitation steel fiber permeable concrete: Figure 4 It can be seen that the best mechanical property is the corrugated polypropylene imitation steel fiber, and the best is the 30mm long corrugated polypropylene fiber, whose flexural strength is 4.12MPa, which is 26.38% higher than the flexural strength of comparative example 1 (test block without added fiber).
[0140] Stress-strain diagram of polypropylene imitation steel fiber permeable concrete: Figure 5 It can be seen that compared with comparative example 1 (without adding polypropylene imitation steel fiber), the strain value of the test block when reaching the peak strength is reduced, and the strain reaches the minimum at 30mm corrugated polypropylene imitation steel fiber. The maximum strain value of the test block after adding polypropylene imitation steel fiber is 42.1% lower than the strain of the test block without fiber addition. It can be seen that the addition of polypropylene imitation steel fiber can improve the rigidity of permeable concrete.
[0141] Porosity and water permeability coefficient of polypropylene imitation steel fiber: tested in accordance with the Technical Specifications for Permeable Cement Concrete Pavement (CJJ / T134-2009). Figure 6 It can be seen that as the fiber length increases, it gradually decreases. When the compressive strength is the highest, the water permeability coefficient of the test block is 5.95mm / s, which still has good water permeability. Figure 7 It can be seen that with the increase of fiber length, the porosity of permeable concrete decreases. When the fiber length is 30 mm, the porosity is 22.61%, which is within the designed porosity range.
[0142] Electron microscope scanning image of polypropylene imitation steel fiber permeable concrete after destruction: Figure 8 This is an electron microscope scan of the damaged polypropylene imitation steel fiber permeable concrete. Figure 8 It can be seen that compared with the original microscopic morphology of the fiber, the roughness of the fiber surface of smooth, embossed and wavy polypropylene imitation steel fibers increased significantly when they were pulled out of the matrix, and all of them had scratches and fiber damage to varying degrees. Figure 8 (a) It can be seen that: the smooth surface has fiber peeling and a few fibers are scraped off, and the hydration product is not obviously attached, indicating that the bonding between the fiber and the matrix is not tight enough. Figure 8 (b) It can be seen that the embossed surface has groove-like longitudinal scratches, the fiber is slightly scratched, and some hydration products are attached to the fiber surface. Figure 8 (c) It can be obtained that: the wavy surface roughness increases, the longitudinal and tangential channel scratches are intertwined, causing large-area fiber scratches, and the scratches are deep and the scratch amplitude is large, achieving a similar cutting effect on the fiber surface, and a large amount of hydration products are evenly distributed on the fiber surface. The addition of these three types of fibers effectively increases the difficulty of fiber debonding and sliding from the cement matrix, and significantly improves the strength of permeable concrete. The greater the degree of surface scratches on the fiber when it is destroyed, the greater the friction between the fiber surface and the matrix. At the same time, the hydration products attached to the fiber surface can produce a superposition effect with the channel scratches, enhancing the mechanical meshing effect and interfacial bonding strength between the fiber and the matrix, thereby achieving the maximum peak load and energy dissipation, and further improving the strength.
[0143] At the same time, for the reinforcing component provided by the present invention, which includes ethyl orthosilicate, acrylic acid and silane coupling agent, the specific principle analysis is as follows:
[0144] Improve the interfacial bonding properties of concrete:
[0145] Ethyl orthosilicate is converted into a silicate network through hydrolysis reaction, which combines with the silicate in concrete to improve the connection strength within the aggregate.
[0146] Acrylic acid introduces a new bonding mode between inorganic fillers and polymers, enhancing interfacial adhesion by forming polyacrylates.
[0147] Silane coupling agents effectively connect inorganic fillers to the polymer matrix, improving the overall consistency and durability of the material.
[0148] Mechanical properties of enhanced materials:
[0149] The reinforcing components help to increase the tensile, compressive and flexural strength of concrete, helping to improve the structural integrity and flexibility.
[0150] The surface of polypropylene imitation steel fiber is modified by silane coupling agent so that the fiber can be better combined with the concrete matrix.
[0151] Improve the microstructure density of concrete:
[0152] The silicon dioxide generated by the hydrolysis of ethyl orthosilicate fills the micropores in the concrete, making the structure more compact and reducing the porosity of the material.
[0153] Silane coupling agents can improve the concrete's resistance to penetration and protect the structure from water and harmful substances.
[0154] Increase the material's resistance to environmental corrosion:
[0155] The reinforcing components help improve the acid and alkali resistance and weather resistance of concrete, and help extend its service life in harsh environments.
[0156] Improve the crack resistance of concrete:
[0157] The addition of polypropylene imitation steel fiber has a "microcrack control" effect, which can produce a pull-out and bridging effect when microcracks are formed to prevent crack propagation.
[0158] Improve construction efficiency and quality:
[0159] By adjusting the proportions of the various components in the reinforcing components, ideal concrete workability can be obtained, which facilitates pouring and molding, reduces bubbles and defects, and ensures construction quality.
[0160] In summary, the reinforcing component provided by the present invention can improve the structural performance and durability of concrete while also improving construction efficiency and quality, making polypropylene imitation steel fiber permeable concrete a more excellent building material.
[0161] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0162] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A polypropylene imitation steel fiber permeable concrete, characterized in that: The polypropylene imitation steel fiber permeable concrete includes the following raw materials in parts by weight: The reinforcing components include the following components in parts by weight: 45 parts of ethyl orthosilicate, Acrylic acid 50 parts, Silane coupling agent 6 parts; The aggregate gradation of the melon seed stone is 5mm-10mm; The cement is ordinary Portland cement with a strength grade of PO 42.5; The content of the silica fume is as follows: by weight percentage, 1.2%-1.5% iron oxide, 2%-4% aluminum oxide, 1.6%-2.4% calcium oxide, 0.3%-0.8% magnesium oxide, and the balance is silicon dioxide; The water reducing agent is produced by BASF AG of Germany. FS20 type water reducing agent; The smooth polypropylene imitation steel fiber has a length of 15mm-45mm, a diameter of 0.8mm, a tensile strength of 540MPa, and an elastic modulus of 6000MPa; The silane coupling agent is 3-methacryloxypropyltrimethoxysilane or vinyltrimethoxysilane.
2. A method for preparing polypropylene imitation steel fiber permeable concrete as claimed in claim 1, characterized in that: The following steps are involved: (1) All the melon seeds used in the test were cleaned to remove surface sand and impurities, dried in a drying oven and sieved to obtain a single size; (2) pouring the melon seed stone, cement, silica fume, reinforcing component, and water reducing agent obtained in step (1) into a single-horizontal shaft mixer and stirring and mixing them thoroughly to obtain a premix; adding water to the premix and continuing to stir until the slurry has good fluidity and no dry material is visually observed to obtain a mixture; (3) dispersing the smooth polypropylene imitation steel fiber into multiple uniform portions, and gradually adding the portions into the mixture obtained in step (2) to obtain a fiber mixed slurry; (4) placing the mold coated with a release agent in advance on a vibration table, placing a pre-assembled baffle around the outer edge of the mold, injecting the fiber mixed slurry mixed in step (3) into the mold, turning on the vibration table, and after the vibration is completed, gently scraping off the excess slurry with a scraper and leveling the top surface; (5) After pouring, cover with plastic film, cure at room temperature for 72 hours and then demould. Place the demoulded specimen in a standard curing box and cure in water at a constant temperature of 20±2℃ until the specified age.
3. The method for preparing polypropylene imitation steel fiber permeable concrete according to claim 2, characterized in that: The drying temperature in the drying oven in step (1) is 85°C; The stirring speed of the premix in step (2) is 20 rpm; The stirring time of the premix in step (2) is 60s; The stirring speed of the mixture in step (2) is 20 rpm; The stirring time of the mixture in step (2) is 120s.
4. The method for preparing polypropylene imitation steel fiber permeable concrete according to claim 3, characterized in that: In step (3), the stirring time of the fiber mixed slurry when adding each portion of smooth polypropylene imitation steel fiber is 15 seconds; The vibration time in step (4) is 3s.
5. The method for preparing polypropylene imitation steel fiber permeable concrete according to claim 4, characterized in that: The age period specified in step (5) is 28 days.
Citation Information
Patent Citations
Organic steel-imitating fiber polymer concrete and preparation method thereof
CN113880527A
Basalt fiber reinforced cement based material and preparation method therefor
CN105541208A
Frost-resistant concrete and preparation method thereof
CN108623246A